Early Results of Total Knee Arthroplasty Using a Built-in 3-Degree External Rotation Prosthesis - Choi, Young-Joon (The Korean Knee Society, 2013)
PURPOSE: We compared the outcomes of total knee arthroplasty (TKA) using the Genesis II prosthesis in which 3° of external rotation was incorporated into the femoral component and Nexgen LPS prosthesis in which the degree of external rotation was determined by the extent of intraoperative bone cutting. MATERIALS AND METHODS: Of the patients who underwent TKA for osteoarthritis between November 2006 and December 2009, 326 patients (572 knees) were included in this study. The prosthesis of choice was Genesis II in 199 knees and Nexgen LPS in 373 knees. The mean follow-up was 27 months (range, 24 to 51 months). The American Knee Society score (KSS) and function score (FS) were used for clinical assessments. The maximum flexion angle and patellar tilt were compared between the groups. RESULTS: At the final follow-up, no significant intergroup difference was observed regarding the KSS (p=0.217), FS (p=0.238), maximum flexion angle (p=0.124), and patellar tilt (p=0.156). CONCLUSIONS: There was no significant difference in the clinical outcomes and patellar tilt between the prosthesis in which 3° of external rotation was incorporated into the femoral component and the prosthesis in which external rotation was determined based on bone cutting.